PENGARUH AIR DALAM AMPAS TEBU TERHADAP KECEPATAN PENYALAAN DALAM PEMBAKAR PUTAR - Syahrul Aiman (Jurnal Kimia Terapan Indonesia, 1991)
The pyrolysis of sugar cane bagasse at peak temperatures between 300 and 1100 "C and at heating rates of 200 - 10,000 °Cjs produced water, primary tar, C02 and char. Further decomposition of the primary tar resulted gases and secondary tar. The conversion of dry bagasse to volatile materials was 91.6 %. Bagasse water content influenced the pyrolysisproducts composition. It decreased the maximum yield of secondary tar from 50.6 to 39.8 %, increased total gas yield from 34.5 to 54.7 % and ultimate char yield from 8.4 to 11.7 % (of theinitial dry sample weight). For combustion  engineeringpurposes, a singlefirst order reaction model with E = 12.9 kcai/mole, A = 3.33 x 1& s·1 and W· = 88.7 % was a suitable model to predict bagasse pyrolysis reaction rate based on the total weight loss data. The calculation indicated that water in bagasse-decreasedignition rate in a bagasse swirl burner.